No on Prop 6 Fundraiser in Watkins Family Backyard - Watkins, Howard::::::::: (1978)
Audience listening to musicians, seated: Art Agnos, Cantor Michael Loring, June Loring, Bernie Meyerson, Marian Meyerson; standing Donna McKittrick, Evo Bluestein, ??, Lois Lyness, ? Ruth Wall, Helen Wilson, Janice Pearson, Jackson Grote, Raul Martinez, Linda Gomez